Generation Z’s Perceptions of Balinese Traditional Beverages as Culinary Tourism Attractions - I Gusti Agung Febrianto; Setyowati Ayu Widuri; I Nyoman Gede Agus Jaya Saputra; I Ketut Rusdiarnata; Ni Kadek Eni Juniari (Journal of Sustainable Tourism and Entrepreneurship, 2026)
Purpose: This study aimed to explore Generation Z’s perceptions of Balinese traditional beverages as a culinary tourism attraction. Research Methodology: A quantitative descriptive approach was employed using an online questionnaire distributed to respondents aged 18–27 years with prior experience consuming traditional Balinese drinks. This study examined several aspects, including taste preferences, cultural values, presentation aesthetics, and the influence of social media. Results: The results provide insights into Generation Z’s consumption patterns and interests, informing more effective promotional strategies and product innovations for the brand. They also support the preservation of Balinese culinary culture through approaches that are more adaptive and relevant to younger audiences than traditional ones. Conclusions: The findings indicate that Generation Z generally perceives Balinese traditional beverages positively, particularly in terms of sensory qualities, cultural value, and health benefits, while perceptions of product innovation and social media influence are weaker, suggesting a need for more consistent innovation and strategic digital promotion to strengthen their appeal as culinary tourism attractions. Limitations: This study recommends social media optimization without empirically testing how specific digital marketing tactics influence Generation Z’s perceptions or consumption intentions. Contribution: Future research should evaluate the effectiveness of specific digital marketing strategies in increasing the appeal of traditional beverages to younger consumers and employ longitudinal designs to capture changes in perceptions and behaviors over time as Generation Z’s digital trends and lifestyle preferences evolve.